ANALISIS KOMPOS BERBAHAN DASAR SAMPAH ORGANIK DI LINGKUNGAN KAMPUS DENGAN AKTIVATOR EM4, KOTORAN SAPI DAN KOTORAN UNGGAS DALAM UPAYA MENDUKUNG GERAKAN KAMPUS HIJAU - Nurul Sofa; Gt. Muhammad Hatta; Yudi Firmanul Arifin (Jurnal Hutan Tropis, 2022)
Organic waste which found around Lambung Mangkurat campus is dominated by dried leaves. The falling leaves have been occuring everyday since the campus covered by many kinds of trees. Therefore it is needed a good waste management system, namely to utilize leave waste to be compost by adding different activators. The purpose of study is to examine the fastest activator to decomposer leave waste, and to know if the compost quality produced by each activators accordance to SNI 19-7031-2004 standard. Composting was carried out for 50 days with treatment (P1) without activator; (P2) chopped leaves + cow dung; (P3) chopped leaves + chicken manure; and (P4) leaf chopped + EM4. The method used was a compIeteIy randomized design method and the data analysis used was a compIete randomized design diversity analysis. This study consisted of 4 treatments with 3 replications. Parameters carried out include pH, moisture content, C-Organic, total N, C / N ratio, Phosphorus (P), Potassium (K), Iron (Fe). The results of the research for 50 days showed that the fastest composting time was compost with cow dung activator, namely coarse decomposition occurred at week 3 and observation of the pH of all treatments did not meet the SNI standards because above the SNI determined for pH. And for the K content in treatment P1 (without treatment) 0.09% and P4 (EM4) 0.11% did not meet the SNI for potassium levels because it was below 0.20%. The final result of compost using cow manure and chicken manure as activator meets SNI 19-7-30-2004 more than without activator and activator EM4.